PENERAPAN SOLAR CELL TERHADAP PERINGATAN DINI BENCANA BANJIR BERBASIS IoT - Masthura Masthura; Nazaruddin Nasution; Muhammad Rajali Harahap (Komunikasi Fisika Indonesia, 2023)
The purpose of this research is to find out how to design and build a flood early warning system so that it can be connected to the internet network can directly send information, design the Blynk application so that it can receive information, and to find out the flood early warning system that has been built using solar panels. The design of an internet of things-based water level monitoring tool using the blynk application requires several components, namely, arduino uno wifi, ultrasonic sensor HC-SR04, buzzer, led, LCD, Brushless pump dc, and solar panels. The results of measuring water levels using the HC-SR04 sensor have a low error rate with a comparison of the HC-SR04 sensor with a ruler of 1.97%. The time it takes to send the sensor reading notification is 4.42 seconds. A flood early warning system that is connected to the blynk has been realized, marked by the success of the system in measuring water levels and being able to send notifications to the blynk with the right size and status. There is also the average time of sending messages or data to the blynk application in all conditions using arduino uno WiFi is 4.42 seconds. From the results of testing data on solar panels without a load and using a load, the voltage and current of the solar panels are influenced by weather conditions, if the weather is cloudy, the voltage and current generated by the solar panels will decrease.